MODERN PROTESTANT IDEOLOGY AND DENATIONALIZATION OF NORTH CAUCASIAN PEOPLES (CASE STUDIES OF NORTH OSSETIA AND ADYGEI) - BABICH, Irina (CENTRAL ASIA AND THE CAUCASUS, 2024)
The article aims to compare the religious/ethnic situation in two North Caucasian republics—North Ossetia and Adygei; the place of Protestantism in the regional context, the growing number of Protestant communities (Baptist, Pentecostals, Adventists) in these republics, the emergence of new ideologies of North Caucasian highlanders and the roots of their increasing popularity. The field ethnographic materials gathered in 2009-2019 confirm that the process of denationalization is ongoing despite the efforts of the local public figures to revive and expand the sphere of folk traditions up to and including neo-paganism. A comparison of Protestantism in North Ossetia-Alania and Adygei revealed that the trend towards a new foundation remains the same, while the paths, forms and methods may vary.